Research in phenolic compounds in leaves of non-pharmacopoeial species of the genus Salvia from Ukrainian flora - M. M. Myha; O. M. Koshovyi; T. V. Ilina; N. V. Borodina; M. I. Skybitska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The search for new sources of biologically active substances of phenolic nature is a topic task of the modern pharmaceutical industry and science to expand the domestic raw material base of medicinal plants and to create new medicines based on them.